Effects of geometrical parameters to the performance of louvered fin heat exchangers - Md Seri, Suzairin; Amirnordin, Shahrin Hisham; Woon, Qiu Yik; Hissein Didane, Djamal (Trans Tech Publications, 2015)
Numerical study using ANSYS Fluent is conducted to investigate the effects of louver angle on pressure drop and heat transfer of a heat exchanger. Flow simulations are conducted on 3D modeling of multi stacks louvered fins at three different parameters of louver angles which are 22.0º, 25.5º and 29.0º with Reynolds number ranging from 200 to 1000. These Reynolds numbers are based on louver pitch and fin pitch. The flow temperature is set at 300K which is the room temperature, while temperature of louver fin is set at 400K. The results show that Reynolds number based on fin pitch 2.02 mm and louver angle of 22.0º generate higher performance of heat exchanger compared to louver pitch of 1.40 mm and the other louver angles. Therefore, configuration of Reynolds number based on fin pitch 2.02 mm and louver angle 22.0º is preferred to be adopted in the design process of heat exchanger.